The Effect of Apium graveolens (Linn) Extract on Reepithelialization of Incision Wounds: In Vivo Study - Muhammad Avicenna Abdul Syukur; Endang Mahati; Vega Karlowee; Hermawan Istiadi; Indah Saraswati; Najatullah; Muflihatul Muniroh (HM Publisher, 2023)
Background: A wound is a disorder of the continuity of the epithelial layer of the skin or mucosa and can result from physical or thermal damage. Proliferation and remodeling processes are important phases in incision wound healing. Celery is believed to have the potential to regulate the inflammatory phase and accelerate the process of proliferation and remodeling of wound tissue. This study aims to evaluate the potency of celery extract (Apium graveolens (Linn)) on incision wound healing in vivo. Methods: This study was an in vivo experimental study. A total of 24 rats were used in this study and divided into 4 treatment groups (2 control and 2 treatment groups). Analysis of epithelial thickness ratio and epithelial length was performed using SPSS using univariate and bivariate. Results: The control group had the lowest epithelial thickness ratio, followed by 50% extract, 75% extract, and finally, the gentamicin group. The length of newly formed epithelium in wounds treated with Apium graveolens (Linn) extract group 70% (mean 1.461 mm) was similar to that treated with gentamicin 0.1% (mean 1.457 mm) and much better than those treated without extract (0.869 mm). Conclusion: Celery extract (Apium graveolens (Linn)) has the potential to accelerate the process of reepithelialization of incision wounds in vivo studies.